Prognostic value of prognostic nutritional index in patients undergoing surgery for gastric cancer - Mülküt, Fırat; Ofluoğlu, Cem Batuhan; Başdoğan, Mustafa Kağan; Aydın, İsa Caner; Akdoğan, Osman; Gündoğdu, Adnan; Subaşı, İsmail Ege (Frontiers in Surgery, 2025)
Background and aimGastric cancer is among the commonly occurring cancers worldwide and is one of the leading causes of cancer-related deaths. Malnutrition is an important factor affecting the course of disease and treatment response in gastric cancer patients this study aimed to investigate the effect of the Prognostic Nutritional Index (PNI) on postoperative complications and long-term survival in gastric cancer patients, and to comparatively examine PNI values among different histological subtypes.MethodsData from patients who underwent curative surgical resection for gastric cancer between 2014 and 2020 were retrospectively analyzed. PNI values were calculated using the formula: 10 × serum albumin (g/dl) + 0.005 × lymphocyte count (cells/mm3). The optimal cut-off value for PNI was determined through ROC analysis. The relationship between PNI values and clinicopathological features, postoperative complications, 5-year overall survival (OS), and histological subtypes was evaluated.ResultsA total of 220 patients (161 males, 59 females; mean age: 60.63 ± 10.56) were included in the study. The mean PNI value was 47.15 ± 6.07. ROC analysis established an optimal PNI cut-off value of 46.2 (AUC = 0.673, 95% CI: 0.599-0.747, p<0.001; sensitivity 78.8%, specificity 51.9%). Complication rates were significantly higher in the patient group with PNI < 46.2 (p = 0.006). The 5-year OS rate was 30.0%. Patients with low PNI values had significantly shorter survival (log-rank p = 0.001). Major complications were more frequent in patients with low PNI (p = 0.006). Patients diagnosed with signet ring cell carcinoma (SRCC) had significantly lower PNI values compared to other adenocarcinoma subtypes (p = 0.001). PNI values were lower in the presence of perineural invasion (p = 0.005) and lymphovascular invasion (p = 0.032). In multivariate analysis, tumor stage (for Stage I p = 0.01, Stage II p = 0.034, Stage III p = 0.002) and PNI value (p = 0.001) were identified as independent prognostic factors affecting 5-year OS. Conclusion: PNI is an important marker for predicting long-term survival and postoperative complication risk in patients with gastric cancer. The significantly lower PNI values in the SRCC subtype compared to other histological subtypes indicate the necessity of closer monitoring of nutritional status in this patient group. Our results suggest that preoperative PNI assessment could be a valuable parameter in planning patient-specific treatment approaches.